Proximate, Total Phenolic, Antioxidant Activity and Amino Acids Profile of Bali Indigenous Chicken, Spent Laying Hen and Broiler Breast Fillet - Okarini , Ida Ayu; Purnomo, Hari; Aulanni`am,; Radiati, Liliek Eka (International Journal of Poultry Science, 2013)
Fresh chicken breast fillet of Bali indigenous chicken, spent laying hen and broiler were studied for proximate, total phenolic, antioxidant activity and its amino acids profile. Broiler breast fillet contained higher moisture, fat, and ash contents (P